Day-Ahead Optimal Dispatching of Wind-Solar-Thermal Power Storage System Considering Deep Peak Shaving of Thermal Power - Xiongwei LI; Xin WANG; Jiawei GU; Jiahao XU (Zhongguo dianli)
Realizing the complementary operation of wind, solar, and thermal power storage by deeply mining the deep peak-shaving capacity of thermal power units is an important means to deal with the large-scale grid-connected consumption of new energy. This paper proposes the calculation methods of the deep peak shaving and climbing cost of thermal power units, pollutant penalty cost, operation cost of the energy storage system, and penalty cost of new energy power abandonment. In addition, it builds the day-ahead optimal dispatching model of the wind-solar-thermal power storage system considering deep peak shaving of thermal power. Taking the maximum wind and solar output, the minimum net load fluctuation, and the lowest system operation cost as the optimization objectives separately, this study simulates and calculates the optimal dispatching strategies of the wind-solar-thermal power storage system with a high proportion of new energy on a typical day under different peak-shaving depths of thermal power units. The results show that the built model can realize the calculation of the optimal dispatching strategies of wind, solar, and thermal power storage under different optimization objectives. A larger deep peak-shaving capacity of thermal power units can effectively reduce the power abandonment rate of new energy.